(untitled) (Global Journal of Science Frontier Research, 2016)
Up to the present time a lot of interesting hypotheses of Multiverses have been offered. However, their common shortcoming is the fact that even in the distant future they will not be able to obtain experimental confirmation. They can not be refuted either. In other words, they are unverifiable. I.e. they are in fact non-existent for us. As opposed to them, the hypothesis of the hidden Multiverse considered in the article is completely verifiable, because its physical reality can be confirmed experimentally already now. This hypothesis is based on the principle of physical reality of imaginary numbers repeatedly proven by the author, which has allowed establishing a number of fundamental errors in the generally accepted version of the special relativity theory. Eliminating these errors allowed to offer a corrected relativistic formula, based on which the hidden Multiverse hypothesis was created, named in such a way because all the parallel universes included in it are mutually invisible. The reason for their invisibility is explained. It is established that such invisible universes are dark matter and dark energy. It is shown where in the hidden Multiverse the different types of antimatter are located. The data obtained by WMAP and Planck spacecrafts allowed to determine the parameters and structure of the hidden Multiverse, which proved to be a quaternion.